Randomized Double Blind Comparison of Two Brands of Clopidogrel in Inhibition of Platelet Aggregation - AA, Azeemi (Journal of Medical Biomedical and Applied Sciences, 2014)
To compare the anti platelet effects of locally manufactured clopidogrel with the anti platelet effect of clopido-grel manufactured by multinational pharmaceutical abroad.